Comparative Analysis of Juvenile Criminal Liability: The Indonesian and Malaysian Approaches to Defence of Infancy - Muh Endriyo Susila; Stephanie Devty (Faculty of Law Universitas Jenderal Soedirman, 2026)
The minimum age at which children can be held criminally liable is a central issue in juvenile criminal justice because it reflects how the law defines childhood, liability, and the state’s obligations toward child offenders. This study examines how Indonesia and Malaysia design and apply the defence of infancy and how these choices influence the treatment of children in conflict with the law. The study aims to analyse the conceptual foundations, mechanisms, and practical consequences of the minimum age for establishing criminal liability in both jurisdictions. This study relies entirely on secondary data drawn from legislation, judicial decisions, academic literature, and official documents. Indonesian materials include the Juvenile Justice System Law of 2012 and several illustrative judgments, such as Decision Number 23/Pid.Sus-Anak/2025/PN Lbp, Decision Number 127/Pid.Sus/2012/PN.Bi, and Decision Number 1/Pid.Sus-Anak/2022/PN.Sbr. Malaysian sources include the Child Act of 2001, the Malaysian Penal Code, and case law such as Child v Public Prosecutor [2020] MLJU 13944. The findings show that Indonesia adopts a fixed statutory minimum age of twelve accompanied by diversion and restorative justice mechanisms, while Malaysia applies the doctrine of doli incapax, granting absolute immunity to children under ten and a rebuttable presumption for those aged ten to twelve, with greater reliance on institutional rehabilitation. These differences shape how liability is assessed and how children are processed, rehabilitated, and reintegrated into society. Based on these observations, the study suggests that Malaysia could benefit from expanding restorative practices, while Indonesia requires stronger and more consistent implementation of its existing restorative framework.